2007
DOI: 10.1152/jn.00310.2007
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of Action History in the Rat Ventral Striatum

Abstract: In a dynamic environment, animals need to update information about the rewards expected from their alternative actions continually to make optimal choices for its survival. Because the reward resulting from a given action can be substantially delayed, the process of linking a reward to its causative action would be facilitated by memory signals related to the animal's previous actions. Although the ventral striatum has been proposed to play a key role in updating the information about the rewards expected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 46 publications
6
30
0
Order By: Relevance
“…The activity of NAc neurons modulated by different actions during the execution of the poking (action-coding neurons) might code either differences in the physical movements or differences in the spatial position of rats. This notion is consistent with previous reports showing that the responses of a subset of NAc neurons changed with different choices of actions in discrimination tasks and a spatial-delayed matching-to-sample task (Chang et al, 2002;Kim et al, 2007;Taha et al, 2007). In the current study, we found evidence that information related to action lasted beyond the timing of reward delivery after the choice.…”
Section: Modeling Rats' Choice Behaviorsupporting
confidence: 93%
“…The activity of NAc neurons modulated by different actions during the execution of the poking (action-coding neurons) might code either differences in the physical movements or differences in the spatial position of rats. This notion is consistent with previous reports showing that the responses of a subset of NAc neurons changed with different choices of actions in discrimination tasks and a spatial-delayed matching-to-sample task (Chang et al, 2002;Kim et al, 2007;Taha et al, 2007). In the current study, we found evidence that information related to action lasted beyond the timing of reward delivery after the choice.…”
Section: Modeling Rats' Choice Behaviorsupporting
confidence: 93%
“…This idea is also consistent with "actor-critic" models of ventral striatal areas during reinforcement learning, in which the striatum contributes to the estimation of internal state values that are compared against incoming sensory information on future trials in order to generate appropriate error signals (O'Doherty et al 2004). Consistent with this model, ventral striatal neurons thought to be connected to medial prefrontal and orbitofrontal areas have been shown to modulate their firing patterns based on choices made in the previous trial (Kim et al 2007), suggesting that these neurons retain a memory trace of previous decision outcomes in order to update expected outcomes on the current trial. It remains unclear whether this form of temporal continuity in firing rates is also present in dorsal striatal neurons near the region that was active in the present study.…”
Section: Discussionsupporting
confidence: 62%
“…As another possibility, which is not mutually exclusive to the scenario above, the estimate of reward-based arming probability (i.e., action value function estimated according to a simple RL algorithm) and the latest run length might be separately computed before being combined to estimate the final stacked arming probability. Physiological studies have found neural signals that are related to action value functions that were computed based on a simple RL algorithm Samejima et al 2005;Seo and Lee 2007) and neural signals that are related to animal's previous choice Kim et al 2007;Seo and Lee 2008) or the number of selfexecuted actions (Sawamura et al 2002) in cortical and subcortical brain structures. The latter may represent the latest run length in the DAWH task.…”
Section: Discussionmentioning
confidence: 99%